SOCIAL WELFARE SCHEMES BASED ON MOBILE APPLICATIONS:A STUDY - Mr. Jesly Anto. J, Dr. Gladson Clifford Joe. C, Mr. Muhammed Ashraf (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Welfare is considered as a residuary element that remains to be provided only after ensuring basic needs like health, housing, medical relief, education, employment, social security, recreation and relief measures in emergency. Social services are meant for normal population whereas social welfare services are required by the vulnerable sections of the society which include service for differently abled, underprivileged women, children and backward classes. The aim of social welfare schemes is to enable the weaker sections of the community to reach a stage where they too can benefit from the available social services. Social reform also belongs to the realm of welfare. Its objectives are to remove the social evils which effect various sections of the society like superstitions and thoughtless rituals. Social security refers to the governmental protection for those who lose income because of age, unemployment or death. Our final aim is for a classless society with spiritual values of service and selflessness. Social welfare programmes covers family welfare, youth welfare, services for the differently abled, service for military veterans, disaster relief, community development, medical and services, psychiatric social services, school and services and correctional services. In the present day context, social welfare is taken to the next level through the concept of E-governance. Target population is covered through various governance tools. The dawn of the 21st century has also brought in the advancements in science to enable people to share the various schemes aimed at them through various tools and techniques. There are numerous schemes which have gone digital. Many of the schemes have unique apps which is designed and provided to the masses through Mobile Seva, which is citizens services on mobile phones and is an initiative of Government of India. Gone are the days when online platforms were used to